63.7k views
3 votes
Simplify the following expression. 12a^3b^6c^5/3a^2b^4c^5

A. 4ab^2
B. 9ab^2c
C. 9ab^2
D. 4ab^2c

User Dan Beam
by
6.4k points

2 Answers

3 votes

Answer:

A. 4ab^2.

Step-by-Step Explanation.

12 a^3 b^6 c^5 / 3 a^2 b^4 c^5

Dividing each pairs of terms:

12 / 3 = 4.

a^3 / a^2 = a.

b^6 / b^4 = b^2.

c^5 / c^4 = 1.

So it is 4ab^2.

User Yorel
by
5.5k points
3 votes
Is this how your problem is written (see attached image) If so, the answer is A. 4ab^2
User Sten Ka Razin
by
5.8k points